Mechanism of the HIP bonding of Zircaloy-4 in the alpha-phase field - Hill, P; Todd, R; Ridley, N (2003)
The HIP bonding of as-received annealed Zircaloy-4 sheet of relatively large grain size has been investigated at elevated temperatures (770-810 degreesC) in the alpha-phase field. Studies of plastic flow behaviour showed that the material had a constant strain rate sensitivity of flow stress, m similar to 0.2, (n similar to 5) over a wide range of strain rates. The activation energy over this temperature range was consistent with power law creep as the rate controlling process for deformation. Bonding studies at 800 degreesC showed that interface void closure occurred by constrained plastic collapse and diffusion. The progressive increase of plastic constraint during void closure led to a dominance of diffusion. When the constraint of inter-void ligaments was introduced into an earlier model, this gave an improved agreement between prediction and experiment for diffusion bonding (DB) of the alpha-phase. (C) 2002 Elsevier Science B.V. All rights reserved.